Opportunistic management of estuaries under climate change: A new adaptive decision-making framework and its practical application. (1st November 2015) - Peirson, William; Davey, Erica; Jones, Alan; Hadwen, Wade; Bishop, Keith; Beger, Maria; Capon, Samantha; Fairweather, Peter; Creese, Bob; Smith, Timothy F.; Gray, Leigh; Tomlinson, Rodger
Abstract: Ongoing coastal development and the prospect of severe climate change impacts present pressing estuary management and governance challenges. Robust approaches must recognise the intertwined social and ecological vulnerabilities of estuaries. Here, a new governance and management framework is proposed that recognises the integrated social-ecological systems of estuaries so as to permit transformative adaptation to climate change within these systems. The framework lists stakeholders and identifies estuarine uses and values. Goals are categorised that are specific to ecosystems, private property, public infrastructure, and human communities. Systematic adaptation management strategies are proposed with conceptual examples and associated governance approaches. Contrasting case studies are used to illustrate the practical application of these ideas. The framework will assist estuary managers worldwide to achieve their goals, minimise maladaptative responses, better identify competing interests, reduce stakeholder conflict and exploit opportunities for appropriate ecosystem restoration and sustainable development. Highlights: A practical method for climate adaptation of estuaries is presented. This method encompasses economic, social and ecological facets. This is the first comprehensive compilation of estuary uses and values. This is the first compilation of a comprehensive list of estuary stakeholders. Tactics and strategies for management of estuaries and stakeholders are presented. .